2023
DOI: 10.3390/nu15153480
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stunting among Children under Five in Pakistan

Abstract: Introduction: Child stunting remains a public health concern. It is characterized as poor cognitive and physical development in children due to inadequate nutrition during the first 1000 days of life. Across south Asia, Pakistan has the second-highest prevalence of stunting. This study assessed the most recent nationally representative data, the National Nutrition Survey (NNS) 2018, to identify the stunting prevalence and determinants among Pakistani children under five. Methods: The NNS 2018, a cross-sectiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The study's findings indicate that moms with less education run a higher chance of producing children who are stunted. This is consistent with a study conducted in 2023 by Soofi et al, [21] which found that children whose moms have less education are more likely to experience stunting. Children born to mothers with poor levels of education are 1.57 times more likely to be stunted [22].…”
Section: Maternal Factorssupporting
confidence: 92%
“…The study's findings indicate that moms with less education run a higher chance of producing children who are stunted. This is consistent with a study conducted in 2023 by Soofi et al, [21] which found that children whose moms have less education are more likely to experience stunting. Children born to mothers with poor levels of education are 1.57 times more likely to be stunted [22].…”
Section: Maternal Factorssupporting
confidence: 92%
“…Feeding infants with different milk formulas and the early introduction of solid foods were important factors in early life stages that favor the development of obesity in children [ 69 ]. Generally, child undernutrition is a global development problem resulting from poor access to nutritious foods, repeated infections, and inadequate maternal and child feeding and care practices during the first 1,000 days, from conception to age two [ 70 ]. In the first 1000 days of life, it was observed by some studies that boys reported having a higher prevalence of both wasting and stunting [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%